Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Karyawan pada CV. Inti Baja Beton Cipayung Depok - Wulandari, Ko’o Haryati; Dinantara, Mohamad Duddy (Jurnal Disrupsi Bisnis, 2024)
The purpose of this study is to determine the influence of compensation and work environment partially and simultaneously on the performance of CV employees. Cipayung-Depok Concrete Steel Core. The method used was a quantitative method of descriptive approach with a sampling technique using the slovin technique with a population of 165 employees and a sample of 62 respondents was obtained. The results of hypothesis-1 testing obtained a t-value of 8.142 > t table 2.00100) and a Sig. value of 0.000<0.05. This means that partially the compensation variable has a significant positive effect on employee performance. The results of hypothesis 2 test obtained a t-value of 8.994 > t-table 2.001 and a Sig. value of 0.000 < 0.05. This means that partially the work environment variable has a significant positive effect on employee performance. The results of hypothesis 3 testing obtained a value of Fcal 66.748 > Ftable 3.15. This means that simultaneously the compensation variables and the work environment have a significant positive influence on employee performance.